Pediatric Palliative Care for Children with Progressive Non-Malignant Diseases - Siden, Harold (Children (Basel), 2018)
A substantial number of children cared for by pediatric palliative care physicians have progressive non-malignant conditions. Some elements of their care overlap with care for children with cancer while other elements, especially prognosis and trajectory, have nuanced differences. This article reviews the population, physical-emotional and social concerns, and trajectory.